GROUP COUNSELING USES COGNITIVE BEHAVIOR THERAPY (CBT) APPROACHES TO INCREASE CAREER MATURITY - Shella Satiwi Guci; Netrawati (Yayasan Citra Dharma Cindekia, 2021)
Teenage is an important phase in the developmental period, especially regarding the ability to make decisions about his future career choices. Career decisions will be easily achieved if students have good career maturity. Group counseling is a service that can help students overcome obstacles in career maturity. The research method used is a literature review that is supported by data from several articles, source books, and other supporting documents. Guidance and counseling teachers can apply group counseling services to overcome career problems. One approach that can be used in order to help the career maturity of students in group counseling is an approach that focuses on changing negative thoughts and maladaptive beliefs (CBT) that are owned by students. The results of the study showed that group counseling services with the Cognitive Behavior Theraphy (CBT) approach can be effectively help in solving the career problems of students.